PROFIL PERMAINAN TRADISIONAL MOTELA - Ardiansyah D Kandupi; Nurmin Sakaria; Nurjannah . (Jurnal Ilmu Pendidikan Jasmani Kesehatan Dan Olahraga, 2020)
The purpose of this study was to determine the profile of the traditional motela game. This research is expected to provide an understanding for readers and writers about the traditional game of Redi Pap motela. The data collection technique used is direct observation. The results of this study indicate that the traditional motela game adapted directly from the petanque sport is a past sport by the Tolaleo tribe. The traditional motela game was created based on the history of Tojo Una-Una Regency, which continues to promote the traditional motela game. This game originated before 1945 which was carried out at my padaku or peasants' party activities. This game is a team game. The definition of Motela is to hit bamboo with a bat until it hits a target which is also made of bamboo. The game is a team game, there are two types of Motela games, namely Tela Dote and Tela Baya.